The Efficacy of Cannabis in Reducing Back Pain: A Systematic Review. Issue 2 (February 2022) - Price, Richard L.; Charlot, Kaarina V.; Frieler, Sven; Dettori, Joseph R.; Oskouian, Rod; Chapman, Jens R.
Objective: To critically analyze the evidence and efficacy of cannabis to treat surgical and nonsurgical back pain via a Systematic Review. Methods: We conducted a systematic review to investigate the efficacy of cannabis to treat non-surgical and surgical back pain. A literature search was performed with MEDLINE and Embase databases. Only RCTs and prospective cohort studies with concurrent control were included in this study. Risk of bias and quality grading was assessed for each included study. Results: Database searches returned 1738 non-duplicated results. An initial screening excluded 1716 results. Twenty-two full text articles were assessed for eligibility. Four articles ultimately met pre-determined eligibility and were included in the study. Two studies addressed post-SCI pain while other two studies addressed low back pain. No studies specifically examined the use of cannabis for surgical back pain. The type of cannabis varied between study and included THC, dronabinol, and Nabilone. A total of 110 patients were included in the four studies reviewed. In each study, there was a quantifiable advantage of cannabis therapy for alleviating back pain. There were no serious adverse effects reported. Conclusions: In all articles, cannabis was shown to be effective to treat back pain with an acceptable side effect profile. However, long-term follow up is lacking. As medicinal cannabis is being used more commonly for analgesic effect and patients are "self-prescribing" cannabis for back pain, additional studies are needed for healthcare providers to confidently recommend cannabis therapy for back pain. Study Design: Systematic review.